2021
DOI: 10.1016/j.sjbs.2021.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Ecological analysis and environmental niche modelling of Dactylorhiza hatagirea (D. Don) Soo: A conservation approach for critically endangered medicinal orchid

Abstract: The natural populations of Dactylorhiza hatagirea have been greatly affected due to incessant exploitation. As such, studies on its population attributes together with habitat suitability and environmental factors affecting its distribution are needed to be undertaken for its conservation in nature. Present study aimed at accessing an impact of anthropogenic pressure on population structure and locate suitable habitats for the conservation of this critically endangered orchid. Considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Elevation and temperature are often the most determining variable in habitat modelling. Research conducted by Wani et al (2021) showed the variable that influences habitat modelling of Dactylorhiza hatagirea is elevation. Kolanowska (2013) states that the most influential variable in habitat modelling of Oeceoclades maculata is temperature.…”
Section: Model Performance and Contributions Of Environmental Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevation and temperature are often the most determining variable in habitat modelling. Research conducted by Wani et al (2021) showed the variable that influences habitat modelling of Dactylorhiza hatagirea is elevation. Kolanowska (2013) states that the most influential variable in habitat modelling of Oeceoclades maculata is temperature.…”
Section: Model Performance and Contributions Of Environmental Variablesmentioning
confidence: 99%
“…The diversity of the orchid family is inseparable from the uniqueness of its generative propagation, symbiosis with microorganisms, and various types of habitats where they could grow. However, because it has an association with specific pollinators and microorganisms and limitation of germination, many orchids have limited distribution (Swarts and Dixon 2009;Wani et al 2021). Some orchids species are becoming threatened by several factors, such as overgrazing, habitat loss, human intrusion, and over-exploitation due to increasing market demand in trading (Pant and Raskoti 2013;Agustini et al 2016;Warghat et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To design an effective conservation strategy for any species of plants, information about its reproductive behavior and pollination ecology along with other threatening factors becomes imperative [ 16 , 17 ]. Scientific data generated in such studies help in designing conservation strategies on one hand and in exploring the mechanism by which it has become endangered on the other [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it requires only species presence data, can deal effectively with limited occurrence data and small sample sizes, and can use continuous and categorical environmental data as input variables. Numerous studies have predicted changes in animal and plant distributions in response to contemporary climate changes using the Maxent model [7,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%